The variant CLCN1_c.1775A>C was not Identified in Brazilian Quarter Horses - Rocha Lago, Glauder [UNESP]; Maria Santos Sperandio, Lídia [UNESP]; Garrido Albertino, Lukas [UNESP]; Secorun Borges, Alexandre [UNESP]; de Oliveira-Filho, José Paes [UNESP] (Universidade Federal do Rio Grande do Sul, 2024)
Background: Congenital myotonia is a genetic neuromuscular disorder characterized by delayed relaxation of the musculature following a strong contraction. Variants in the skeletal muscle chloride channel 1 gene (CLCN1) have been linked to this disorder across several species. The CLCN1_c.1775A>C, an autosomal recessive variant, was identified as a potential causative factor for congenital myotonia in New Forest Pony. While the CLCN1_c.1775A>C variant has been studied in different breeds of horses, it remains unexplored in Brazilian Quarter Horses. Therefore, this study aimed to assess the prevalence of the CLCN1_c.1775A>C variant among Brazilian Quarter Horses across various disciplines. Materials, Methods & Results: In this study, 96 DNA samples were obtained from athletic Brazilian Quarter Horses representing various disciplines, 24 each from cutting, reining, barrel racing, and bull-cacthing (“vaquejada”). DNA viability was assessed via PCR targeting the β-actin gene. Subsequently, a previously described set of specific primers was employed to amplify the region encompassing the CLCN1_c.1775A>C variant. The resulting purified PCR products underwent Sanger direct sequencing, and their electropherograms were analyzed. Notably, none of the horses in this cohort were found to carry the CLCN1_c.1775A>C variant. The inbreeding coefficient (F) was calculated using pedigree data sourced from the 96 Quarter Horses according to Brazilian Quarter Horse Breeders Association records encompassing 4 generations. The average F value for the entire cohort was found to be 0.2%. However, when assessed across disciplines, the average F values varied, with cutting at 0.002 (0.2%), reining at 0.003 (0.3%), barrel racing at 0.0008 (0.08%), and bull-cacthing at 0.001 (0.1%), respectively. Notably, within this cohort, 48 horses were identified as inbred, exhibiting an average F of 1.5%. Discussion: Genetic variants associated with conditions such as hyperkalemic periodic paralysis, myosin heavy chain myopathy, and polysaccharide storage myopathy type 1 have been previously documented in Quarter Horses globally, including Brazil. However, as in the present study, the CLCN1 c.1775A>C variant was also not detected in American Quarter Horses affected by muscular disorders. Although this variant has been implicated as the cause of congenital myotonia in a New Forest pony, its correlation with cases of congenital myotonia in Quarter Horses has not been established yet. Although the inbreeding coefficient and the prevalence of endogamous horses observed in this study were lower compared to findings in other studies, the presence of inbreeding and shared ancestors within Quarter Horses lineages was evident. High rates of inbreeding may disseminate undesirable genetic variants, since popular stallions may improve the athletic performance of its progenies but also may transmit alleles with pathogenic variants, as seen in other genetic disorders in horses. Differently, since it was not observed in this group of evaluated Quarter Horses nor in other previous studies, it may be that the CLCN1 c.1775A>C is a 'de novo' variant related strictly to congenital myotonia in the New Forest pony. Nevertheless, it is imperative to highlight the potential for congenital myotonia to inflict significant harm upon horses. Investigations into new cases are essential to establish both clinical and etiological diagnoses, thereby enabling the assessment of the requisite preventive measures against this disorder.
Keywords: CLCN1; equestrian industry; genotyping; variants